A Calcifying Odontogenic Cyst Associated with Compound Odontoma Mimicking a Tooth Germ. (28th June 2021) - Oliveira, Eduardo Morato; Santana, Lucas Alves da Mota; Silva, Erika Rezende; Souza, Leandro Napier
Abstract : Calcifying odontogenic cyst (COC) is a rare cyst that affects mainly the anterior region of the jaws. Generally, it appears as a unilocular radiolucent lesion containing peripheral foci of calcification, but with radiographic variations depending on the type of presentation. Here, we report an atypical case of COC associated with odontoma, initially diagnosed as a tooth germ, in the posterior region of the mandible of a 10-year-old male patient. Interestingly, the radiographic aspect appeared as a unilocular radiolucent lesion without peripheral foci of calcification in the edentulous region, having its size increased after traction of the impacted tooth adjacent to that area. Thus, the case presented in this study is aimed at calling dentists' attention to its developmental changes and related pathologies.